2017
DOI: 10.4172/2168-9849.1000160
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Alexithymia in the General Adult Population of Quetta, Balochistan in Pakistan

Abstract: Alexithymia is recognized as a medical condition in which an individual fails to express his feelings rather suppressing their thoughts and face difficulties in distinctive emotions leading to a number of neuropsychiatric issues. By means of measuring emotional intensity based on the professed reality of external stimuli, inferences could be drawn to indicate distinctive response patterns of such individuals. Therefore incidence of alexithymia was studied in the general adult population of Quetta Balochistan b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 33 publications
0
9
1
Order By: Relevance
“…Secondly, the sample for this study comprised male university students. Numerous studies have revealed gender differences concerning alexithymia, calling attention to the prevalence of alexithymia in men when compared with women (Khan, 2017; Levant et al, 2009; Salminen et al, 1999). In addition, studies have also shown that university students are not only at a greater risk of developing mental health disorders (Naz et al, 2017), but psychiatric disorders are also most prevalent in those students with substance use, anxiety, and mood disorders (Pedrelli et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the sample for this study comprised male university students. Numerous studies have revealed gender differences concerning alexithymia, calling attention to the prevalence of alexithymia in men when compared with women (Khan, 2017; Levant et al, 2009; Salminen et al, 1999). In addition, studies have also shown that university students are not only at a greater risk of developing mental health disorders (Naz et al, 2017), but psychiatric disorders are also most prevalent in those students with substance use, anxiety, and mood disorders (Pedrelli et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In the last few years, the soft drinks industry is continuously increasing and elevated to the standard level of $2 billion. Its growth rate is increased up to 18% till 2009 (Khan, 2009). …”
Section: Literature Reviewmentioning
confidence: 99%
“…Ahmad (2003) revealed that all over Pakistan almost 170 beverage industrial units are working at present. Beverages industrial production reached a level of $2 billion during last years (Khan, 2009). People living in Pakistan consume non-alcoholic beverages to a great extent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 7 Single or isolated individuals, those who lack family support, and populations with low socioeconomic status all have a higher risk of developing alexithymia. 11 , 13 Face-to-face relationships and social, linguistic, and neuroscience exploration have been suggested in previous studies as possible treatments by which alexithymia might be improved. 2 , 16 Despite the significance of alexithymia, there are few studies regarding its prevalence and associated factors in Saudi Arabia.…”
mentioning
confidence: 99%